Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1997
DOI: 10.1115/97-gt-120
|View full text |Cite
|
Sign up to set email alerts
|

Aero-Thermal Performance Measurements and Analysis of a Two-Dimensional High Turning Rotor Blade

Abstract: The purpose of this contribution is to report on the aerothermal performance measurements and calculations carried out around a high pressure gas turbine rotor blade profile mounted in a two-dimensional linear cascade arrangement. The measurements were performed in the CT-2 facility of the von Karman Institute, allowing a correct simulation of the operating conditions encountered in modern aero-engines. Independent variations of exit Mach (0.8 … 1.3) and Reynolds numbers (5 105 … 2 106), free stream turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Predicted rotor profile loss was consistent with current design practice. Arts et al (1997), Dunn et al (1994), and Blair (1994) among others, showed midspan rotor blade leading edge heat transfer rates nearly twice the highest values seen elsewhere on the blade. Civinskas et al (1990) showed heat transfer in this region was reduced using a large leading edge diameter, and aerodynamic losses were not significantly increased.…”
Section: Fig 1 Transonic Turbine Blade Cascadementioning
confidence: 85%
“…Predicted rotor profile loss was consistent with current design practice. Arts et al (1997), Dunn et al (1994), and Blair (1994) among others, showed midspan rotor blade leading edge heat transfer rates nearly twice the highest values seen elsewhere on the blade. Civinskas et al (1990) showed heat transfer in this region was reduced using a large leading edge diameter, and aerodynamic losses were not significantly increased.…”
Section: Fig 1 Transonic Turbine Blade Cascadementioning
confidence: 85%
“…The stator cases chosen were from Arts et al (1990), and from Hylton et al (1983). The rotor cases presented were those of Arts et al (1997). These data show rotor surface heat transfer for a range of Mach numbers, Reynolds numbers, and rotor incidence angles.…”
Section: Data Comparisonsmentioning
confidence: 99%
“…The entire blade might be manufactured in ceramic for cascade testing (Arts et al [27]), or inserts could be fitted into metallic blades in the case of measurements on the rotor of a turbine stage (Dénos [28]). …”
Section: Measurement Technique Thin Film Gaugesmentioning
confidence: 99%